Apoyo en el área contable para la empresa Armony Clean Company S.A.S. Bic (2022)
Accounting is born from different actions of people who had some type of property. Leading to find a way to keep a record of each of them, there is evidence of different actions recorded by subjects which reflected movements in their records acquiring goods or exchanging them. Accounting is said to be born in the world's first civilization. Over time, the exercise of accounting has evolved as the new ways of relating to the economy, the development of new regulatory frameworks, seeking to standardize a single language in accounting matters, new forms of control of the Tax Administration and the application of different platforms and software from different national, territorial and local entities. The purpose of this work is to analyze and strengthen the accounting, financial and organizational area of the company Armony Clean Company S.A.S BIC, which has as its corporate purpose the provision of commercial, industrial, office cleaning services, tank maintenance services and locative maintenance, commonly known as toderos. This strengthening will make it possible to apply the various knowledge acquired in the career, keeping an organizational control of each process that intervenes at the time of providing the service, suggesting improvements in the different processes and procedures in the accounting and administrative area, in order that the information financial information is timely and complies with the principles contained in the conceptual framework of the IFRS, to strengthen decision-making in the organization